2019
DOI: 10.1159/000503723
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor and Supraoptic Vasopressin Neurons in Hyponatremia

Abstract: Hyponatremia due to elevated arginine vasopressin (AVP) secretion increases mortality in liver failure patients. The mechanisms causing dysregulation of AVP secretion are unknown. Our hypothesis is that inappropriate AVP release associated with liver failure is due to increased brain-derived neurotrophic factor (BDNF) in the supraoptic nucleus (SON). BDNF diminishes GABA A inhibition in SON AVP neurons by increasing intracellular chloride through tyrosine receptor kinase B (TrkB) activation and downregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 57 publications
(131 reference statements)
1
12
0
Order By: Relevance
“…This was consistent with our previous studies. 17,18,39,41 Also, plasma osmolality and hematocrit values in the BDL rats were significantly lower than those from sham rats.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…This was consistent with our previous studies. 17,18,39,41 Also, plasma osmolality and hematocrit values in the BDL rats were significantly lower than those from sham rats.…”
Section: Discussionmentioning
confidence: 82%
“…phospho-KCC2 (pKCC2). 39 This was associated with the increased plasma AVP and dilutional hyponatremia observed in liver cirrhosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Fluid intake and urine excretion were greater in BDL rats despite their low plasma osmolalities, suggesting a possible role for non-osmotic mechanisms in drinking behavior of BDL rats. Previous studies from our laboratory have shown that angiotensin type 1 receptors in the subfornical organ and BDNF in the SON contribute to increased fluid intake in male BDL rats [10, 32, 45, 57]. Sex differences were observed in fluid intake and urine excretion of BDL rats.…”
Section: Discussion/conclusionmentioning
confidence: 82%